(untitled) (Indian Journal of Arid Horticulture, 2025)
Correlation at genotypic and phenotypic levels along with path coefficient analysis were studied for various yield and its component characters in twenty genotypes of pea (Pisum sativum L.) during rabi 2009-10. Analysis of variance revealed significant differences for all the characters, indicating the presence of good variability in the studied genotypes. Correlation studies showed that green pod yield per plant was positively and significantly associated with pod length, pod weight, and number of grains per pod. Path coefficient analysis revealed that traits such as the number of pods per plant, pod weight, number of grains per pod, number of pickings, and protein content were the most important for selecting high-yielding genotypes, as they exerted a high positive direct effect and had a positive correlation with green pod yield per plant. These findings suggest that these traits should be considered major yield-contributing traits in pea breeding programs.